Immunorecognition of the 14F7 Mab Raised against N-Glycolyl GM3 Ganglioside in Some Normal and Malignant Tissues from Genitourinary System. (16th August 2011) - Blanco, Rancés; Cedeño, Mercedes; Escobar, Xiomara; Blanco, Damián; Rengifo, Charles E.; Frómeta, Milagros; Alvarez, Rosa Irene; Rengifo, Enrique; Carr, Adriana
Abstract : N-glycolyl neuraminic acid has been considered as a tumour-associated antigen forming both glycolipid and glycoprotein, expressed in some human malignant cells. In this work, we evaluate the 14F7 Mab (an IgG1 murine highly specific to N-glycolyl GM3 ganglioside) reactivity in a variety of genitourinary-system-derived tumors as well as in their normal counterparts. Immunohistochemical assays with 14F7 followed by anti-mouse biotinylated antibody and ABC/HRP system using formalin-fixed and paraffin-embedded tissues were carried out. In normal tissues, 14F7 was reactive only in renal tubules of kidney (2/6) and in the stromal component and blood vessels of ovary (3/5). Tumors of kidney (12/38), urinary bladder (8/9), breast (41/42), ovary (21/34), testis (4/5), prostate (17/20), and uterus (5/14) as well as prostatic nodular hyperplasia (5/8) were stained with 14F7. N-glycolyl GM3 recognized by 14F7 could be considered as one attractive target for both active and passive immunotherapy of genitourinary malignancies expressing this molecule.